2021
DOI: 10.1038/s41467-021-22374-y
|View full text |Cite
|
Sign up to set email alerts
|

Modular synthesis of chiral 1,2-dihydropyridines via Mannich/Wittig/cycloisomerization sequence that internally reuses waste

Abstract: Abstract1,2-Dihydropyridines are valuable and reactive synthons, and particularly useful precursors to synthesize piperidines and pyridines that are among the most common structural components of pharmaceuticals. However, the catalytic enantioselective synthesis of structurally diverse 1,2-dihydropyridines is limited to enantioselective addition of nucleophiles to activated pyridines. Here, we report a modular organocatalytic Mannich/Wittig/cycloisomerization sequence as a flexible strategy to access chiral 1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…Traditionally, synthetic access to partially saturated nitrogen heterocycles (e.g. dihydropyridines) has relied on various cyclization and cycloaddition reactions and dearomatization of heteroarenes. For example, azatrienes prepared through condensation of carbonyl compounds and amines or through transition metal-catalyzed reactions undergo 6-π electrocyclization to deliver 1,2- or 2,3-dihydropyridines ,, and hetero Diels–Alder reactions can deliver 1,4-dihydropyridines . These cyclization and cycloaddition approaches use starting materials that require multistep synthesis and allow preparation of only certain substitution patterns on dihydropyridines due to the steric and electronic requirements of these reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, synthetic access to partially saturated nitrogen heterocycles (e.g. dihydropyridines) has relied on various cyclization and cycloaddition reactions and dearomatization of heteroarenes. For example, azatrienes prepared through condensation of carbonyl compounds and amines or through transition metal-catalyzed reactions undergo 6-π electrocyclization to deliver 1,2- or 2,3-dihydropyridines ,, and hetero Diels–Alder reactions can deliver 1,4-dihydropyridines . These cyclization and cycloaddition approaches use starting materials that require multistep synthesis and allow preparation of only certain substitution patterns on dihydropyridines due to the steric and electronic requirements of these reactions.…”
Section: Introductionmentioning
confidence: 99%
“… 2 Despite substantial advances, this strategy only modifies the periphery of the dearomatized pyridine molecules by tuning the substituents while retaining the six-membered cyclic structure. 3 Skeletal re-editing is an important complementary method that comprises two elementary steps: deconstruction of the underlying molecular skeleton to generate reactive species and subsequent reconstruction to deliver structurally distinct molecules. This method rapidly and reliably achieves skeletal diversity by modifying the core framework.…”
Section: Introductionmentioning
confidence: 99%
“… 11 Very recently, Yu, Zhou et al reported the enantioselective synthesis of 1,2-dihydropyridines, using a chiral amine catalyst. 12 Metal-free protocols that allow rapid access to substituted DHPs and their derivatives are in high demand.…”
mentioning
confidence: 99%
“…Tejedor et al has developed a convenient domino access to substituted alkyl 1,2-dihydropyridine-3-carboxylates from propargyl enol ethers and primary amines by means of a Claisen rearrangement/isomerization/amine condensation/6π-aza-electrocyclization process (Scheme c) . Very recently, Yu, Zhou et al reported the enantioselective synthesis of 1,2-dihydropyridines, using a chiral amine catalyst . Metal-free protocols that allow rapid access to substituted DHPs and their derivatives are in high demand.…”
mentioning
confidence: 99%